2008
DOI: 10.1093/toxsci/kfn221
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium-Induced Differential Toxicogenomic Response in Resistant and Sensitive Mouse Strains Undergoing Neurulation

Abstract: Common inbred mouse strains, such as the C57BL/6 (C57) and the SWV, display differences in sensitivity to environmental teratogens during gestation. For example, the C57 is more sensitive than the SWV to cadmium (Cd) exposure during neurulation, inducing a higher incidence of neural tube defects (NTDs). Here, we report, using Cd as a model teratogen, the first large scale toxicogenomic study to compare teratogen-induced gene expression alterations in C57 and SWV embryos undergoing neurulation, identifying toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 46 publications
8
64
1
1
Order By: Relevance
“…Even if the pollutant concentrations were lower and might not lead to acute toxicity, but their sub-acute, chronic, and genetic toxicities also may be harmful on animals exposed to YZR-SDW-NJ for a lifetime. It is because that the low-dose exposures with the organic pollutants could alter the cell cycle, MAPK signaling pathway, TGF-b signaling pathway, aberrant of cell cycles at least and lead to tumor progression and malignant transformation (Massague 2008;MacDonald et al 2009;Andrew et al 2007;Perez et al 2008;Robinson et al 2009;Cebrat et al 2004;Jacobson et al 2010;Johanson et al 2007;Bespalova et al 2010;Makarov et al 2009). Selecting of seed genes from the differently expressed genes (DEGs)…”
Section: Resultsmentioning
confidence: 99%
“…Even if the pollutant concentrations were lower and might not lead to acute toxicity, but their sub-acute, chronic, and genetic toxicities also may be harmful on animals exposed to YZR-SDW-NJ for a lifetime. It is because that the low-dose exposures with the organic pollutants could alter the cell cycle, MAPK signaling pathway, TGF-b signaling pathway, aberrant of cell cycles at least and lead to tumor progression and malignant transformation (Massague 2008;MacDonald et al 2009;Andrew et al 2007;Perez et al 2008;Robinson et al 2009;Cebrat et al 2004;Jacobson et al 2010;Johanson et al 2007;Bespalova et al 2010;Makarov et al 2009). Selecting of seed genes from the differently expressed genes (DEGs)…”
Section: Resultsmentioning
confidence: 99%
“…The DEGs associated with MAPK signaling pathway included crk, prkca, gadd45b, ppp3cc, gadd45g, cacna1f and egfr. It has been indicated that low-dose exposure to arsenic [30] and cadmium [31] can significantly alter the regulation of mouse MAPK signaling pathway. Usually, activation of this pathway can promote cell division, and aberrance of MAPK has been implicated in several human diseases including inflammation and cancers [32].…”
Section: Discussionmentioning
confidence: 99%
“…Cell cycle is a typical biological pathway and can be easily altered by carcinogenic contaminants such as disinfection by-products [28], arsenic [30], cadmium [31] and benzo(a)pyrene [38]. TA was also found to induce bladder epithelial cell proliferation in rats [39].…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that maternal Cd exposure causes relatively specific forelimb ectrodactyly (the deficiency or absence of one or more central digits) in mouse strains when administered during early limb development (Robinson et al, 2009(Robinson et al, , 2011. Cdinduced fetal malformations might be associated with impairment of placental development and a reduction in placental transport capacity.…”
Section: Reactive Oxygen Speciesmentioning
confidence: 99%